Предмет: Математика,
автор: nozimasalomova752
a^4-2a^3b-8a^2b^2-6ab^3-b^4
Разложить на множители
Ответы
Автор ответа:
0
Ответ: (a+b)((a-b)(a²+b²)-2ab((a+b)+2b²)
Решение:
a⁴-2a³b-8a²b²-6ab³-b⁴=a⁴-b⁴-2ab(a²+4ab+3b²)=(a²-b²)(a²+b²)-2ab((a+b)²+2b²)=(a-b)(a+b)(a²+b²)-2ab((a+b)²+2b²)=
=(a+b)((a-b)(a²+b²)-2ab((a+b)+2b²)
Похожие вопросы
Предмет: Українська література,
автор: si6359569
Предмет: История,
автор: h24013
Предмет: Биология,
автор: Аноним
Предмет: Русский язык,
автор: yliamironova
Предмет: Математика,
автор: Аноним